Prediction of Ambient Weather Conditions of Alexandria Governorate by Mathematical Relationships - Yacout*, Dalia M. M. (CURRENT APPLIED SCIENCE AND TECHNOLOGY, 2018)
As the most populated country in both North Africa and Middle East regions, Egypt is facing an up scaling demand in increasing its agricultural productivity. One of the main challenges which faces the production of plants in Egypt is the lack of information regarding the effect of microclimate on plant’s productivity. The prediction of ambient weather conditions is essential for conducting further investigation to determine the effect of microclimate on plant’s yield. The current work presents the development of prediction equations that could simulate the trend of outside conditions. A computer program was employed to describe the trend of ambient-air conditions throughout an entire year in Alexandria Governorate, Egypt. Weather data of Alexandria governorate for five consecutive years was used in this analysis. Statistical analysis of daily hourly changes for air temperatures and relative humidities based upon metrological data revealed that the monthly average was the best descriptive measure to the month. Also an attempted to identify a representative day to simulate every season was investigated, however, results show that such indicator could not be introduced due to highly significant difference between weather conditions within the months of each season. By employing a computer model based on Fourier series, mathematical expressions were developed to predict on an hourly basis outside air temperatures and air relative humidity throughout a representative day for each month within the year. Correlation coefficient for accuracy was taken into consideration as well. The developed prediction equations can be used in future investigations in various areas which require weather conditions as inputs, such areas as environmental control, agriculture and food storage and handling. Keywords: Simulation, Prediction Equations, Ambient-Air Conditions, Air Temperature, Relative Humidity Email: dalia.yacout@gmail.com